Intermittently “Pre-Excited” ECG after Accessory Pathway Ablation: Unsuccessful Procedure or a Complication? - Evgeny Mikhaylov; Elnara Voitkovskaya; Dmitry Lebedev (Case Reports in Cardiology)
A 52-year-old woman with previously unsuccessful posteroseptal pathway ablation using radiofrequency energy presented with intermittently occurring short PR followed by a wide QRS complex, and complaining of palpitations with characteristics different from previous history. During a second electrophysiological procedure no signs of preexcitation were found. Ventricular discharges with fusion with sinus beats were revealed, and catheter ablation of premature contractions originating from the proximity to previous accessory pathway was carried out.